Coaching Dalam Agenda Habituasi Ditinjau Dari Model GROW - Machmudan (Pusat Pendidikan dan Pelatihan Perdagangan, 2020)
Training supported by coaching was convinced as effective method to increase personell or organization performance. Pre service training for civil servant candidate also using coaching as method in habituation agenda, but is not use specific coaching model, coaching is not effective yet to increase civil servant candidate performance in habituation agenda. This study aims to describe coaching in habituation agenda in pre service training related goal, reality, option, and will. This study is literature study research by qualitative approach, using GROW coaching model formulating by Sir John Whitmore. The data were collected using literature study and document. Result of the study found that: coaching in habituation agenda related by goal including understanding goal, setting goal, and result in habituation agenda; reality including define organization issue, setting creative problem solving, deciding solution in actualization plan; option including set activities and step of activities, output, analyzing relations between activities with civil servant basic value, analyzing relations between activities with vision and mission of organization, analyzing relations between activities with strengthening organization value and actualization plan seminar presentation; and will including implementing of actualization, reporting, and actualization seminar presentation. It is neccesarry to coach in habituation agenda for coach and coachee related by goal, reality, option, and will in appropriate quality and skillful coaching.